Go Green Culture in Selametan Katerbi’en Tradition of Madura: Budaya Go Green dalam Tradisi Selametan Katerbi'en Madura - Mailawati Mailawati; Intan Elok Okti Wardani; Hendrokumoro (Diglossia: Jurnal Kajian Ilmiah Kebahasaan dan Kesusastraan, 2023)
Humans have been preserving nature even before the popularisation of the go-green movement. This research plays a substantial role in confessing natural elements in reducing global warming. This research used a qualitative approach to reveal the correlation between environments and languages. Besides, tradition is not only inherited local wisdom, but in-depth, it consists of wise messages behind. This data analysis through the triangulation of validity data produced eco-lexicons, semiotic interpretations, and the ancestral ideologies of the Madurese community. The discussion identified that the Madurese tradition assimilated with the Javanese tradition in preserving environments viewed from several similarities. It means there is also an ideological resemblance between these both. In the end, knowing the messages inside this tradition will provide a broader understanding of the ancestors' beliefs that humans need to protect nature. This research also suggests the possibility of shared messages between two or more intersecting cultures. Keywords: culture, semiotics, ideology, ecolinguistics.